Facet-dependent catalytic activity of two-dimensional Ti3C2Tx MXene on hydrogen storage performance of MgH2 - Gao, Haiguang; Shi, Rui; Liu, Yana; Zhu, Yunfeng; Zhang, Jiguang; Li, Liquan; Hu, Xiaohui (Journal of magnesium and alloys, 2023)
Two-dimensional Ti3C2Tx MXenes exposing different active facets are introduced into MgH2, and their catalytic effects are systematically investigated in depth through experimental and theoretical approaches. Excluding factors such as interlayer space, surface functional groups and experimental contingency, the exposed facets is considered to be the dominant factor for catalytic activity of Ti3C2Tx towards MgH2. More exposed edge facets of Ti3C2Tx displays higher catalytic activity than that with more exposed basal facets, which also leads to different rate-controlling steps of MgH2 in the de/hydrogenation process. The low work function, strong hydrogen affinity and high content of in situ metallic Ti for the edge facet contribute the high catalytic activity. This work will give insights into the structural design of two-dimensional Ti3C2Tx MXene used for enhancing the catalytic activity in various fields.